Protective Effect of Acid protease inplasmodium berghei - Dakhel, khalid Majeed (University of Thi-Qar Journal of Science, 2014)
Acid protease from plasmodium berghei was purified through sephadex G-200. Five fold purification of the enzyme was achieved.The purified enzyme contained mixture of proteins ranging between Molecular weights 27K to 66K .Acid protease induced antibody response in mice and the animals were Partially protected upon challenge . Antiprotease antibodies inhibited about 50% invasion of erythrocytes by merozoites in vitro.